(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
In the context of the national emergency, social dynamics and educational services required actions to ensure the continuity of the teaching and learning process; provoking effects both in the student population and in teaching-administrative populations. Given this scenario, the construction of evidence that describes the effects of the measures taken in the learning processes and in the socio-labor conditions of the profession becomes imperative; as well as the gaps and emerging challenges for educational performance from the perception of educators. In response to this context, the College of Graduates and Professors in Letters, Philosophy, Sciences and Arts (Colypro), together with other instances, carried out a diagnosis of the effects on the socio-labor conditions of the profession and another study on the implications in the incorporation of digital technologies in learning processes. In such a way that, it was possible to establish the educational challenges for the learning process and generate lines of articulated work that respond to the demands detected.